Farewell Luncheon at Cedar Lanes Bowling Alley for Tomar Mason II - Watkins, Howard::::::::: (1986)
Fresno County Clerk Galen Larson, Tomar Mason II's mother-Tomar Mason, Tomar's father: William Mason, Justice Pauline Davis Hanson at head table